Development of Internal Educational Quality Assurance Management Model of Private Schools in Samut Songkhram Province - Jitawat, Pichetpong; Duagchuen , Patcharaporn; Untaweesin, Apinun (Academic MCU Buriram Journal, 2025)
This research has specific objectives to 1) Study the issues in the internal quality assurance management of private schools in Samut Songkhram Province, 2) Design and develop a management model, 3) Evaluate the proposed model, 4) Compare the experimental results before and after implementation, and 5) Examine the effectiveness, efficiency, and value of the model. The sample group included Kongli Jianmin School, an experimental school. The instruments used for data collection were questionnaires, model evaluation forms, experimental plans, pre- and post-experiment evaluation forms, and evaluation forms for model use in terms of efficiency, effectiveness, and value. To provide educational institutions with guidelines for developing internal educational quality assurance from the 5Co-PDCAA model as a prototype to promote the implementation of internal educational quality assurance management and to comply with the specified educational standards effectively. The quality of the instrument was examined by using the consistency test between the questions and the objectives by 5 experts using the consistency score (IOC). It appears that the experts agree with the principles, objectives, processes and goals of the model. The questions are consistent with the set objectives with an internal consistency value (IOC) between 0.80 and 1.00. The statistics used in the research include mean, standard deviation, t-test dependent and content analysis. The research results found that: 1. The overall problem of internal educational quality assurance management in private schools in Samut Songkhram Province is at a high level. 2. The internal quality assurance management model of private schools in Samut Songkhram Province is the 5Co-PDCAA Model, consisting of joint quality development planning, joint implementation of the plan, joint inspection, joint improvement and development, and joint responsibility. 3. The consistency index is at the level of 0.80-1.00. 4. The experimental results found that after the experiment, it was significantly higher than before the experiment at the statistical level of .01. 5. The results of using the model in terms of efficiency, effectiveness, and value were at the highest level.